The Effectiveness of Using SmartBoard Interactive Toward Learning Innovation in Schools - Anandito Rahayu, Monica; Makmur, Amelia (JIV-Jurnal Ilmiah Visi, 2024)
SmartBoard Interactive is a tool that combines touch and projection technology, allowing teachers and students to interact directly with learning content through touch screens. SmartBoard Interactive is an implementation of Smartclass. Smartclass is the application of the Internet of Things (IoT) in education. The IoT is a network of physical objects connected to the Internet. This research aims to examine the effectiveness of using SmartBoard Interactive in improving learning innovation in schools. The research method is a survey that uses questionnaires. The respondents in this study were teachers and students at elementary, junior high, and high school levels who used SmartBoard Interactive in the daily learning process. The application of SmartBoard Interactive in Learning includes the use of an interactive whiteboard, multimedia, animation, video, and gamification. The results show that the use of SmartBoard Interactive has a positive impact on learning innovation. Teachers stated that it increased student engagement, improved learning motivation, and facilitated better concept understanding. A total of 96.9% of the students showed a positive response to the use of this technology, felt more motivated, and showed a significant improvement in learning outcomes. This research will encourage the wider application of this technology in educational contexts, with the aim of achieving more effective learning outcomes and enhancing students' learning experiences.